2013
DOI: 10.14478/ace.2013.1099
|View full text |Cite
|
Sign up to set email alerts
|

Fast pyrolysis of Medium-Density Fiberboard Using a Fluidized Bed Reactor

Abstract: Fast pyrolysis of medium-density fiberboard was carried out using a fluidized-bed reactor under various conditions to find an optimum pyrolysis condition. When the pyrolysis temperature was varied between 425 ℃ and 575 ℃, the maximum bio-oil yield of 52 wt% was obtained at 525 ℃. The quality of the bio-oil product increased with increasing pyrolysis temperature. Pyrolysis at a high temperature removed significant amounts of oxygenates and acids, producing more valuable species such as aromatics and phenolics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Lately, there has been a growing interest in utilizing oligosaccharides in different applications such as biodegradable oxygen barrier films [38][39][40], emulsifiers [41][42][43][44][45][46][47], thermoplastics [48], hydrogels [49], coatings, or adhesives [50]. The remaining fibrous fraction, on the other hand, might be suitable for production of new fiberboards [51][52][53][54][55][56][57], cellulose nanocrystals [58,59], bioethanol [60,61], biogas, and bio-oil using pyrolysis [62,63]; however, utilization as reinforcement and filler material in wood-plastic compounds (WPCs) [64][65][66] and particleboards [67] has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there has been a growing interest in utilizing oligosaccharides in different applications such as biodegradable oxygen barrier films [38][39][40], emulsifiers [41][42][43][44][45][46][47], thermoplastics [48], hydrogels [49], coatings, or adhesives [50]. The remaining fibrous fraction, on the other hand, might be suitable for production of new fiberboards [51][52][53][54][55][56][57], cellulose nanocrystals [58,59], bioethanol [60,61], biogas, and bio-oil using pyrolysis [62,63]; however, utilization as reinforcement and filler material in wood-plastic compounds (WPCs) [64][65][66] and particleboards [67] has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow the recyclable material to be included directly in the production flow after hydrolysis [41]. Other potential uses for recycled MDF fibers include the manufacture of wood polymer composites [42,43], the isolation of cellulose nanocrystals [44], the production of biogas and bio-oil [45,46], packaging [47][48][49], and so on.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Moezzipour et al [25] have reported that such negative effects on the fibers can be reduced using electrical heating instead of hydrothermal treatments, leading to improved mechanical properties of the newly produced MDF. Other previously investigated potential uses for recovered waste MDF include the production of cellulose nanocrystals [26,27], wood polymer composites (WPC) [28][29][30], bio-ethanol [31][32][33], bio-oil and biogas [34][35][36][37], or the substitution of particles in the middle layer of particle boards [38] as well as insulation or oil spill absorbance applications [39].…”
Section: Introductionmentioning
confidence: 99%